China Promise or Threat? : A Comparison of Culture - Helle, Horst J. (Brill, 2017)
In China: Promise or Threat? Helle compares the cultures of China and the West through both private and public spheres. For China, the private sphere of family life is well developed while behaviour in public relating to matters of government and the law is less reliable. In contrast, the West operates in reverse. The book’s twelve chapters investigate the causes and effects of threats to the environment, military confrontations, religious differences, fundamentals of cultural history, and the countries’ orientations for finding solutions to societal problems, all informed by the Confucian impulse to recapture the lost splendour of a past versus faith in progress toward a blessed future. The West has promoted individualism while China is locked in its kinship society.